Anthocyanin-rich black elderberry extract improves markers of HDL function and reduces aortic cholesterol in hyperlipidemic mice. Issue 4 (11th March 2015) - Farrell, Nicholas; Norris, Gregory; Lee, Sang Gil; Chun, Ock K.; Blesso, Christopher N.
Abstract : The ability of black elderberry to protect against HDL functional impairment and atherosclerosis in apoE −/− mice was evaluated. Abstract : Serum high-density lipoprotein-cholesterol (HDL-C) is a risk factor considered to be protective of atherosclerosis. However, atherosclerosis is an inflammatory disease and contributes to impairment in high-density lipoprotein (HDL) function, including reductions in HDL-C, HDL antioxidant and anti-inflammatory activities. Anthocyanins are polyphenols that have demonstrated antioxidant and anti-inflammatory properties. The objective of this study was to determine whether an anthocyanin-rich black elderberry extract ( Sambucus nigra ) (BEE) (13% anthocyanins) would protect against inflammation-related impairments in HDL function and atherosclerosis in apoE −/− mice, a mouse model of hyperlipidemia and HDL dysfunction. We fed an AIN-93M diet supplemented with 1.25% (w/w) BEE or control diet to 10 week old male apoE −/− mice for 6 weeks. The BEE fed to mice was rich in cyanidin 3-sambubioside (∼9.8% w/w) and cyanidin 3-glucoside (∼3.8% w/w). After 6 weeks, serum lipids did not differ significantly between groups, while aspartate transaminase (AST) and fasting glucose were reduced in BEE-fed mice. Hepatic and intestinal mRNA changes with BEE-feeding were consistent with an improvement in HDL function ( Apoa1, Pon1, Saa1, Lcat, Clu ) and a reduction in hepatic cholesterol levels (increased Ldlr and Hmgcr, reduced Cyp7a1 ). In BEE-fed mice, serum paraoxonase-1 (PON1) arylesterase activity was significantly higher. In addition, mice fed BEE had significantly lower serum chemokine (C–C motif) ligand 2 (CCL2) compared to control-fed mice. Notably, we observed significant reductions in total cholesterol content of the aorta of BEE-fed mice, indicating less atherosclerosis progression. This study suggests that black elderberry may have the potential to influence HDL dysfunction associated with chronic inflammation by impacting hepatic gene expression.